Effectiveness of Health Education in Improving Mothers' Knowledge of Virgin Coconut Oil (VCO) Massage Therapy to Support Toddlers' Sleep Quality and Health - Lina Ratnasari; Novita Ayu Indraswati; Nita Hestiyana (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Maternal knowledge plays an important role in determining the successful implementation of complementary health interventions for toddlers. Virgin Coconut Oil (VCO) massage therapy has been widely recognized as a safe and affordable complementary practice that may improve children's sleep quality and overall well-being. However, the effectiveness of health education in improving mothers' knowledge and understanding of VCO massage therapy remains inadequately investigated, particularly in primary healthcare settings. Objective: This study aimed to evaluate the effect of health education on mothers' knowledge, understanding, and perceptions regarding Virgin Coconut Oil (VCO) massage therapy for toddlers at Cempaka Public Health Center. Method: A quantitative pre-experimental study employing a one-group pretest–posttest design was conducted among mothers of toddlers. Participants received structured health education regarding the benefits, indications, and proper techniques of VCO massage therapy. Data were collected using validated questionnaires before and after the educational intervention. Descriptive statistics were used to summarize participant characteristics, while changes in knowledge, understanding, and perceptions were analyzed by comparing pretest and posttest scores. Results: Health education substantially improved mothers' knowledge and understanding of VCO massage therapy. The proportion of respondents with good knowledge increased from 40.0% to 86.7%, while understanding of the benefits of VCO massage for improving toddlers' sleep quality increased from 50.0% to 90.0%. Understanding of its potential role in supporting children's health increased from 60.0% to 93.3%, and correct knowledge of massage techniques improved from 46.7% to 83.3%. Furthermore, support for routine implementation of VCO massage therapy increased from 66.7% to 96.7%. The mean knowledge score increased from 62.5 to 85.4, while understanding and perception scores also showed substantial improvement following the intervention. Conclusion: Health education effectively improved mothers' knowledge, understanding, and positive perceptions regarding Virgin Coconut Oil massage therapy for toddlers. Strengthening parental education may enhance the adoption of evidence-informed complementary childcare practices in community healthcare settings.